Pengaruh Online Customer Review dan E-service Quality terhadap Minat Beli pada Marketplace Lazada di Media Sosial Facebook - Ameliawati Rahmadini; Asep Muslihat (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The development of information technology supported by the existence of the internet has caused changes in consumer behavior, namely initially making purchases through offline stores, now switching to shopping through online stores. Therefore, there are now many online shopping places called marketplaces and one of them is Lazada. The purpose of this research is to determine the magnitude of the influence of online customer reviews and e-service quality on buying interest in the Lazada marketplace on social media Facebook. This study uses quantitative methods and technical data analysis in the form of path analysis. The population is Lazada marketplace consumers on social media Facebook with a sample of 100 respondents who were taken using a finite population with the Slovin formula. The data obtained are : (1) There is a very strong correlation between online customer reviews and e-service quality of 0,800. (2) Partially, online customer reviews have a positive and significant effect on buying interest by 34,6%. (3) Partially, e-service quality also has a positive and significant effect on buying interest by 23,1%. (4) Simultaneously, there is an influence between online customer reviews and the e-service quality on buying interest of 57,7%. The rest in the contribution of other variables is equal to 42,3% which was not examined in this study.